2016
DOI: 10.5296/ajfa.v8i2.10274
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Profitability in Ghana: New Evidence

Abstract: This study examines the determinants of profitability in the Ghanaian Banking Industry for an eight (8) year period of 2007 to 2014. Using a sample from 9 local banks and 12 foreign banks in Ghana, the study combines bank-specific determinants and macroeconomic variables to access bank profitability with Return on Assets (ROA) as the dependent variable. The Hausman specification test was performed on a panel regression to determine the appropriate model for this study. The estimation results shows that, bank S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…The results of this study are in accordance with the research of Anarfi, D, who found that the cost of overhead negatively affects ROA. But not in accordance with the results of research from Nouaili, et al, who found no effect of efficiency on ROA [1,16].…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The results of this study are in accordance with the research of Anarfi, D, who found that the cost of overhead negatively affects ROA. But not in accordance with the results of research from Nouaili, et al, who found no effect of efficiency on ROA [1,16].…”
Section: Resultscontrasting
confidence: 57%
“…Other studies related to bank performance using variable Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), Operating Income Operating Costs (BOPO), Non Performance Loans (NPL), Inflation, and Interest Rates have also been done previously [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16], although the results are still different.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Alhassan et al (2016); Demirgüç-Kunt and Maksimovic (1998); Tunay and Silpar (2006); Lipunga (2014); Menicucci and Paolucci (2016) and Regehr and Sengupta (2016) also reached the same conclusion by using different methods in their studies. On the other side, Anarfi et al (2016) and Kolapo et al (2016) concluded that the size of the banks does not have any significant effect on bank profitability.…”
Section: Buchory (2015) Indonesia Regressionmentioning
confidence: 99%
“…They reported that, crude oil price are negatively significant in determining bank profitability whereas total assets is positively significant in explaining bank profitability. Anarfi et al (2016) investigated some key determinants of bank-specific characteristics and macroeconomic indicators and the degree at which they affect banks' profitability in Ghana. The study employed a fixed and random effect model with data obtained from annual financial statements of 21 banks from 2007-2014.…”
Section: Background Of Cocoa Production and Marketing In Ghanamentioning
confidence: 99%